The Use of Social Networks in the Recruitment of New Students in Private Junior High Schools: A Literature Review - Dewi Novita Sari (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2025)
In the digital era, the use of social networks as a medium for recruiting new students both as a promotional tool and as part of the admission process has become increasingly effective. Prospective students can access these platforms remotely, allowing educational institutions to expand their reach beyond geographical boundaries. Student recruitment within formal education management is a routine process aimed at collecting, selecting, and placing students in appropriate educational pathways. Despite being a recurring activity, this process can encounter several challenges that require clear principles and structured guidelines aligned with educational standards. This literature review examines how social networks contribute to enhancing the recruitment process in private junior high schools. The findings indicate that social media platforms not only improve the dissemination of information but also enhance institutional visibility, strengthen engagement with prospective students, and increase the number of new enrollments.